Denture Box, A New Invention In Copy Denture Technique: User Overview - Yacob , Norlela; Abdul Fatah, Faizah (IIUM Medical Journal Malaysia, 2017)
Introduction: Copy denture procedure was introduced in 1962 for the construction of spare denture. However, throughout the years, the procedure has undergone developments in terms of the techniques and materials used for the construction of the replica denture. One of the most popular methods to construct the replica is by using soap box. A group of researchers from USIM have invented Denture Box and the product has been registered with Malaysian Industrial design (MY-16-00546-0101). Therefore, a study was conducted to assess the satisfaction of the Denture Box among dentists and dental technologists. Materials and Methods: Participants who attended the Copy Denture Workshop organized by USIM on 13th April 2017 were asked to make a replica denture from soap-box and Denture Box. A pre-tested questionnaire use 5-point Likert scale was distributed to get their feedback regarding Denture Box after the workshop. Results: Based on their experience during the workshop, all participants (n=41) were satisfied and agreed that the box was 100% practical to use with mean score 4.40±0.49. 92.7% of the participants agreed that the invention can reduce the total cost of denture construction (mean score 4.24±0.57) and 85.5% agreed that Denture Box can save time for denture construction (mean score 4.24±0.71). Interestingly, 87.8% of the participants were excited to use the product in future (mean 4.31±0.67). Conclusion(s): Overall satisfaction from using Denture Box was good. Therefore, Denture Box is ready to be commercialised after some design improvement by taking into consideration a few suggestions made by the participants.